2017
DOI: 10.1021/acsami.6b14618
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Sensitized Graphene/TiO2 Inverse Opal Nanostructures with Enhanced Charge Collection Efficiency for Water Splitting

Abstract: In this contribution we have developed TiO inverse opal based photoelectrodes for photoelectrochemical (PEC) water splitting devices, in which Au nanoparticles (NPs) and reduced graphene oxide (rGO) have been strategically incorporated (TiO@rGO@Au). The periodic hybrid nanostructure showed a photocurrent density of 1.29 mA cm at 1.23 V vs RHE, uncovering a 2-fold enhancement compared to a pristine TiO reference. The Au NPs were confirmed to extensively broaden the absorption spectrum of TiO into the visible ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 60 publications
2
91
0
2
Order By: Relevance
“…Graphene has remarkable charge mobility and provides conductive electron channels for electrons separation, which can inhibit the recombination of photogenerated‐hole pairs due to unpaired π electrons; on the other hand, the graphene can provide synergistic effect, and doping effect with materials to further increase the PEC performance of RGO/materials . In order to enhance the visible light absorption and photocatalytic efficiency, the RGO/semiconductor composite photocatalysts have been extensively researched in current year . Hence, massive articles have been reported that the composites of RGO/ZnO shown great advantages of enhancing photocatalytic activity, photocurrent, photosensitive performance .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has remarkable charge mobility and provides conductive electron channels for electrons separation, which can inhibit the recombination of photogenerated‐hole pairs due to unpaired π electrons; on the other hand, the graphene can provide synergistic effect, and doping effect with materials to further increase the PEC performance of RGO/materials . In order to enhance the visible light absorption and photocatalytic efficiency, the RGO/semiconductor composite photocatalysts have been extensively researched in current year . Hence, massive articles have been reported that the composites of RGO/ZnO shown great advantages of enhancing photocatalytic activity, photocurrent, photosensitive performance .…”
Section: Introductionmentioning
confidence: 99%
“…From the figure S8, ESI and the obtained photovoltaic performance cell parameters (table ), it is seen that the little (0.5 mol %) insertion of Mo(VI) doping into the TiO 2 host lattice of the TiO 2 /RGO NCs, the Jsc value increases abruptly from 16.180 to 18.081 mA/cm 2 and reached the highest Jsc value of 19.656 mA/cm 2 for (Mo 0.100 Ti 0.980 O 1.990 ) 0.925 (RGO) 0.075 NCs based DSSCs. The enhancement of these Jsc value after the addition of doping implies the Mo(VI) doping impurities in the TiO 2 /RGO NCs acts as a charge trapping sites for collection of electrons from the RGO surface liberated from the LUMO of TiO 2 and transferred it to the counter electrode . Also, it may be due to the uplifting in the coverage of the optical region (UV‐Visible) and its higher absorbance strength [figure (x)] after the addition of Mo(VI) doping yields the maximum photon flux of the solar spectrum for the conversion purpose.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the nanostructured electrode design also plays an important role in the PEC efficiency. In recent years, the 3D inverse opal electrodes have demonstrated extraordinary high PEC performance . The light scattering inside the continuous and periodic void structure of the 3D inverse opals enhances light absorption while the large specific surface area of the structure allows the loading of conductive films and light absorber materials .…”
Section: Introductionmentioning
confidence: 99%